2021
DOI: 10.3389/fonc.2021.677051
|View full text |Cite
|
Sign up to set email alerts
|

Doublecortin-Like Kinase 1 (DCLK1) Is a Novel NOTCH Pathway Signaling Regulator in Head and Neck Squamous Cell Carcinoma

Abstract: Despite recent advancements, the 5 year survival of head and neck squamous cell carcinoma (HNSCC) hovers at 60%. DCLK1 has been shown to regulate epithelial-to-mesenchymal transition as well as serving as a cancer stem cell marker in colon, pancreatic and renal cancer. Although it was reported that DCLK1 is associated with poor prognosis in oropharyngeal cancers, very little is known about the molecular characterization of DCLK1 in HNSCC. In this study, we performed a comprehensive transcriptome-based computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
1
16
0
1
Order By: Relevance
“…The multimodality treatment approach for locally advanced OCSCC has evolved over the last few decades, contributing to improvements in functional and esthetic outcomes 54 . However, despite these important advances, therapeutic options remain limited, and complications associated with surgical cancer ablation, long-term effects of radiation, and dose-limiting side effects of systemic cisplatin administration, still have a significant impact on the quality of life in patients with OCSCC 54 .…”
Section: Discussionmentioning
confidence: 99%
“…The multimodality treatment approach for locally advanced OCSCC has evolved over the last few decades, contributing to improvements in functional and esthetic outcomes 54 . However, despite these important advances, therapeutic options remain limited, and complications associated with surgical cancer ablation, long-term effects of radiation, and dose-limiting side effects of systemic cisplatin administration, still have a significant impact on the quality of life in patients with OCSCC 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these previous studies, our current findings are novel in several ways. DCLK1 is best known for its role as a tuft cell and CSC marker in gastrointestinal (GI) cancers, but a mounting body of literature supports its role in promoting non-GI malignancies including breast, lung, head and neck, and others [30,[32][33][34][35][36]. The current study represents, to our knowledge, the first reported study of DCLK1-IN-1 in a non-GI cancer.…”
Section: Discussionmentioning
confidence: 69%
“…Indeed, our prior attempts to use both XMD8-92 and LRRK2-IN-1 in MTT assays with ACHN and CAKI-2 cells (data not shown) demonstrated no effect on viability or proliferation whatsoever, even at concentrations > 100 µM. In contrast, these compounds elicit potent effects against cell viability/proliferation in other cancer types [19,27,30]. Moreover, as further support for this possibility, an examination of gene expression data from the Cancer Cell Line Encyclopedia (CCLE) demonstrates significantly increased expression of MDR1/P-Glycoprotein in all three RCC cell lines (ACHN, 786-O, and CAKI-1 with FPKMs of 5.37, 10.70, and 3.95, respectively) used in this study compared with most lines used in prior DCLK1-IN-1 studies (Patu-8988T, Patu-8902, MKN1, and DLD1 with FPKMs of 0.009, 0.023, 0.046, and 10.4, respectively).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study for rectal NET, NANOG is associated with DCLK1 expression. DCLK1 serves as a new marker for rectal NET in the presence of NANOG as a gene product ( Ikezono et al, 2015 ; Broner et al, 2021 ).…”
Section: Methods To Knockdown Dclk1mentioning
confidence: 99%